A method of moments for exponentials. - O'Brien, Frank; Hammel, Sherry E.; Nguyen, Chung T. (Perceptual & Motor Skills)
A methodological investigation is reported summarizing a substitution method for deriving probability density functions and moments for a class of exponential functions that could be useful to researchers in a variety of disciplines. Reprinted by permission of the publisher, 1995.